2021
DOI: 10.3390/nano11113006
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Protein Nanocomposites as Antimicrobial Agents

Abstract: The use of nanomaterials alone or in composites with proteins is a promising alternative to inhibit pathogenic bacteria. In this regard, this study used seed proteins from both fenugreek (Trigonella foenum-graecum L.) (FNP) and mung bean (Viga radiate) (MNP), with silver nanoparticles (Ag-NPs) and nanocomposites of either Ag-NPs plus FNP (Ag-FNP) or Ag-NPs plus MNP (Ag-MNP) as inhibitory agents against pathogenic bacteria. FNP and MNP were isolated from fenugreek seeds and mung bean seeds, respectively, and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…Several studies reported the isolation of different bacterial pathogens from pickles ( Chaiyasut et al., 2018 ) . Some of these bacterial isolates showed resistance to antibiotics ( Sitohy et al., 2021 ) . This showed an interested challenge to develop pickling processes with complete hygienic procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported the isolation of different bacterial pathogens from pickles ( Chaiyasut et al., 2018 ) . Some of these bacterial isolates showed resistance to antibiotics ( Sitohy et al., 2021 ) . This showed an interested challenge to develop pickling processes with complete hygienic procedures.…”
Section: Discussionmentioning
confidence: 99%
“…They were grown into BHI broth incubated at 37 °C for almost 18h till obtaining actively exponentially growing cells. CFS of L. plantarum LPS10 was added (2% V/V) to these actively growing bacterial cells except control and further incubated at 37 °C for 6 h, then the treated bacterial cells were subjected to TEM analysis as given previously ( Sitohy et al., 2013 , 2021 ; Abdel-Shafi et al., 2016 ) .…”
Section: Methodsmentioning
confidence: 99%
“…A total of about 64 bacterial isolates were obtained. All of these isolates were assayed for antibiotic sensitivity using 13 antibiotics that assimilate 7 antibiotic types such as cephalosporines, polymexins, penicillins, fluroquinolones, aminoglycosides, macrolides, and sulphonamides [ 19 , 20 , 69 ]. Results were taken according to CLSI [ 70 ].…”
Section: Methodsmentioning
confidence: 99%
“…MDR- P. mirabilis is one of the most prevalent microbes to exist in diabetic foot ulcers (DFU) [ 12 ]. There is a vast need to search for other innovative therapies based on using natural plant extract either singly or in combination with antibiotics [ 11 ], probiotics [ 3 , 13 , 14 , 15 , 16 , 17 ], natural and modified proteins [ 18 , 19 ], nanoparticles [ 20 ], and phage therapy [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was demonstrated that green synthesis is a promising method for the production of novel nanopesticides. Sitohy et al developed a different green synthesis approach by combining Ag NPs, which are well known for their antibacterial efficiency, with plant seed proteins to produce nanocomposites with higher antibacterial efficiency than each of the single components [ 2 ]. The proteins acted as stabilizers of Ag and also increased the antibacterial potency of the nanocomposite, plausibly due to positively charged and hydrophobic amino acid residues which facilitated contact with the bacterial cell.…”
mentioning
confidence: 99%